2018
DOI: 10.1007/s10143-018-0974-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of decompressive hemicraniectomy in malignant middle cerebral artery stroke

Abstract: Identification of factors in malignant middle cerebral artery (MMCA) stroke patients that may be useful in selecting patients for DHC. This study was a retrospective multicenter study of patients referred for DHC based on the criteria of the randomized control trials of DHC in MMCA stroke. Demographic, clinical, and radiology data were analyzed. Patients who underwent DHC were compared to those who survived without surgery. Two hundred three patients with MMCA strokes were identified: 137 underwent DHC, 47 sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…About one-third of patients of the cohort had an additional infarction of the ACA/PCA territory, reflecting clinical practice to select patients for hemicraniectomy at our center during the study period. In previous studies, higher MCA infarction volume and occurrence of additional ACA/PCA infarction were shown to be independent predictors for poor outcome in patients with MCA infarction and hemicraniectomy ( 24 , 25 ). Additional ACA/PCA infarction was more frequently observed in patients with poor outcome in our cohort, although not independently predictive for outcome, which is attributable in part to the number of patients included in our cohort.…”
Section: Discussionmentioning
confidence: 87%
“…About one-third of patients of the cohort had an additional infarction of the ACA/PCA territory, reflecting clinical practice to select patients for hemicraniectomy at our center during the study period. In previous studies, higher MCA infarction volume and occurrence of additional ACA/PCA infarction were shown to be independent predictors for poor outcome in patients with MCA infarction and hemicraniectomy ( 24 , 25 ). Additional ACA/PCA infarction was more frequently observed in patients with poor outcome in our cohort, although not independently predictive for outcome, which is attributable in part to the number of patients included in our cohort.…”
Section: Discussionmentioning
confidence: 87%
“…Basal cistern effacement before DC, in particular, is a well-known marker of increased ICP, and one of the most accredited factors affecting prognosis. 5,6,[18][19][20] Fatima et al 18 reported postoperative radiologic markers of decreased ICP (absence of effacement of cortical sulci, absence of compression of the lateral ventricle) and absence of hemorrhagic transformation to be predictors of good neurologic outcomes following MIS. In contrast to this report, we were not able to identify specific patterns of postoperative CT findings to be associated with good neurologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…extent (p=0.001), compression of basal (p=0.02), Sylvian (p=0.02), ambiens (p=0.04), and quadrigeminal cisterns (p=0.01), and the evidence of cerebral herniation (p=0.001). Basal cistern effacement before DC, in particular, is a well-known marker of increased ICP, and one of the most accredited factors affecting prognosis [5,6,[18][19][20]. Fatima et al [18], reported post-operative radiological markers of decreased ICP (absence of effacement of cortical sulci, absence of compression of the lateral ventricle) and absence of hemorrhagic transformation to be predictors of good neurological outcomes following MIS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%